A Operating The Trend of Feminism Research from Perspective of Islam: A Literature Review - Handoko Budi Prasetiyo; Fadil Fadil (Green Publisher Indonesia, 2025)
Feminism is an ideology that advocates for gender equality, emphasizing that men and women are entitled to equal rights across all aspects of life. While Islam also upholds women's rights, equating it directly with feminism can be misleading. Both frameworks share a common emphasis on equality, yet they operate within distinct philosophical and cultural contexts. Islam emphasizes equality before God, particularly in worship and moral responsibility, whereas feminism broadly addresses systemic gender disparities in societal and political realms. This research examines the intersection and divergence between feminist ideology and Islamic principles concerning women's rights. Using a qualitative method with a literature review approach, the study analyzes scholarly works from the Scopus database, published between 2020 and 2024. Findings indicate that recent research tends to focus on women's societal roles, such as maternity, abortion, and marriage, within the scope of either feminism or Islam, but rarely in direct comparison. Moreover, feminist discourse often extends beyond traditional gender roles, demanding broader rights that are not always framed in Islamic discourse. This research contributes to a clearer understanding of where feminism and Islam converge and diverge, offering insights for future interdisciplinary studies on gender, religion, and rights. Further research is recommended to expand the scope beyond Asia and include diverse cultural perspectives.